Parallels and Alliances: The Lived Experiences of Young, Disabled Bisexual People. Issue 2 (2nd April 2020) - Toft, Alex
Abstract: Young people (16–25) who identify as bisexual and disabled have to work against dominant forces of homo/heteronormativity and ableism which regulate sexuality and normalcy. Their lives demonstrate the complex negotiations that must be enacted in order to reside within such restrictive confines. This article uses the lived experience of 15 young (16–25 years) disabled and bisexual identified persons to understand how such identities intersect. Throughout, the voices of young people are centered in order to ensure that their experiences guide the article. Exploration of such life-stories highlights parallels between bisexual and disabled experiences, particularly in terms of misconceptions, erasure/invisibility and how dominant forces are resisted. The article suggests that a bisexual/disabled alliance is potentially fruitful for gaining a more nuanced and detailed understanding of sexuality and disability.